2021
DOI: 10.1002/hep4.1605
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Adenosine Triphosphatase Phospholipid Transporting 8B1 (ATP8B1) Function in Patients With Cholestasis With ATP8B1 Deficiency by Using Peripheral Blood Monocyte-Derived Macrophages

Abstract: Adenosine triphosphatase phospholipid transporting 8B1 (ATP8B1) deficiency, an ultrarare autosomal recessive liver disease, includes severe and mild clinical forms, referred to as progressive familial intrahepatic cholestasis type 1 (PFIC1) and benign recurrent intrahepatic cholestasis type 1 (BRIC1), respectively. There is currently no practical method for determining PFIC1 or BRIC1 at an early disease course phase. Herein, we assessed the feasibility of developing a diagnostic method for PFIC1 and BRIC1. A n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Functional work suggests that residual FIC1 function determines the clinical phenotype of patients with biallelic variants in ATP8B1 , with most patients with early‐onset FIC1 deficiency predicted to have a complete loss of function, and those with benign recurrent intrahepatic cholestasis 5%–20% function of a healthy subject. [ 21 ] The correlation with higher levels of functional FIC1 and phenotype has not been explored, and most patients from our cohort are heterozygotes and therefore have much higher levels of FIC1, at least 50% of healthy subjects. The exact pathogenesis of FIC1 deficiency is not clear [ 22 ] ; however, it appears integral in the role of other proteins, including BSEP, farnesoid X receptor, and cystic fibrosis transmembrane conductance regulator.…”
Section: Discussionmentioning
confidence: 99%
“…Functional work suggests that residual FIC1 function determines the clinical phenotype of patients with biallelic variants in ATP8B1 , with most patients with early‐onset FIC1 deficiency predicted to have a complete loss of function, and those with benign recurrent intrahepatic cholestasis 5%–20% function of a healthy subject. [ 21 ] The correlation with higher levels of functional FIC1 and phenotype has not been explored, and most patients from our cohort are heterozygotes and therefore have much higher levels of FIC1, at least 50% of healthy subjects. The exact pathogenesis of FIC1 deficiency is not clear [ 22 ] ; however, it appears integral in the role of other proteins, including BSEP, farnesoid X receptor, and cystic fibrosis transmembrane conductance regulator.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this difference may also be due to the rare genetic variant of ATP8B1. In a recent Japanese nationwide survey, it was shown that there are no critical methods to distinguish between PFIC1 and BRIC1 at the early phase of the disease (13). Therefore, further accumulation and evaluation of BRIC1 cases are desirable for more appropriate follow-up of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…ATP8B1 mutations reduced BSEP activity and impaired bile excretion by affecting PS turnover ( 13 ). In ATP8B1 deficient patients, the nuclear translocation of the Farnesoid X receptor (FXR), a transcription factor that controls bile acid homeostasis, is disrupted, and BSEP expression on the hepatic duct membrane is reduced due to its transcriptional inhibition ( 14 , 15 ) ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the future, a reliable ATP8B1 protein function detection method is needed to evaluate the severity and prognosis of disease. Research has found that human peripheral blood monocyte-derived macrophages (HMDMs) can be used evaluate ATP8B1 function ( 15 , 26 ).…”
Section: Discussionmentioning
confidence: 99%